Seleksi dan Evaluasi Sorgum Mutan Generasi M2 Hasil Radiasi Sinar Gamma untuk Peningkatan Karakter Biomassa - Yuli Sulistyowati; Ade Nena Nurhasanah; Dwi Widyajayantie; Dwi Astuti; Agus Rachmat; Carla Frieda Pantouw; Vincentia Esti Windiastri; Syamsidah Rahmawati; Satya Nugroho (Politeknik Negeri Lampung., 2022)
Sorghum (Sorghum bicolor L.) is a cereal plant that can adapt to dry area so it has the potential to be developed in Indonesia. Sorghum has many benefits, namely as food, feed and industry. One of the ingredients in sorghum that can be used for industrial materials is lignin which can be used in the manufacture of particleboard and briquettes. In previous studies, selection of lignin content was carried out on 30 genotypes of sorghum and obtained the genotype with the highest lignin content, namely KS (Konawe Selatan). However, the KS genotype has low biomass, so improvements need to be made to increase biomass. Mutation is one way to increase genetic diversity. The purpose of this study was to obtain a sorghum mutant line that had characteristics related to biomass such as plant height, stem diameter and stem weight that were better than the parent. The research was carried out in July – November 2019 at the Citayam Experimental Field. The genetic material used was the M2 mutant lines of 300, 400 and 500 Gy gamma irradiation and 0 Gy control plants. A total of 50 panicles per gray were planted one row per panicle and the agronomic characters were observed. The agronomy observed on the M2 mutant line showed that the population of the 300 Gy mutant line had a wider range of values ​​than the 400 and 500 Gy populations and control. The 300 Gy mutant population also had a higher mean value than the 400 and 500 Gy mutant populations as well as the control on plant height 309.18 cm (control 305.33 cm), stem diameter 24.09 mm (control 19.37 mm), stem weight 860.73 g (control). 507.10 g), panicle length 42.55 cm (control 39.95 cm) and panicle weight 95.52 g (control 64.50 g). Mutations with gamma ray radiation can increase genetic diversity and selection in the M2 mutant lines obtained lines that have plant height, stem diameter and stem weight are better than the control which shows an increase in biomass.